2015
DOI: 10.5539/gjhs.v8n4p127
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life for Elderly Residents in Nursing Homes

Abstract: Background and Objectives:More than 8% of Iran's populations are elderly. The greatest challenge in this generation is improvement of health and QoL. The main goal of this study was QoL for elderly residents in nursing homes over 65 years in Golestan Province - Iran.Methods:This research was an analytical cross study. The population society includes the elderly over 65 years in Golestan Province - Iran. The sample size was calculated based on the correlation of 193 elderly men and women. Therefore, if the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
(25 reference statements)
1
18
0
4
Order By: Relevance
“…Suzana and Charn (2009) also noted that the prevalence of depression among elderly in their study was higher than those reported by Visvanathan et al (2005) who found that 65.0% of elderly people in institutions in Peninsular Malaysia were depressed. Furthermore, it was three to four times higher than the rate observed by Farzianpour et al (2012) among community-dwelling elderly.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Suzana and Charn (2009) also noted that the prevalence of depression among elderly in their study was higher than those reported by Visvanathan et al (2005) who found that 65.0% of elderly people in institutions in Peninsular Malaysia were depressed. Furthermore, it was three to four times higher than the rate observed by Farzianpour et al (2012) among community-dwelling elderly.…”
Section: Introductionmentioning
confidence: 62%
“…Its prevalence among elderly people is common, but it often has been under diagnosed and frequently has been inadequately treated (Kim et al, 2009;Eshagi et al, 2006;Farzianpour et al, 2012). Globally, the prevalence of depression among elderly is 10-15.0% due to such issues as lack of transportation, loss of employment, loss of friends and acquaintances, loss of loved ones, isolation, bereavement and the existence of a variety of health problems (Krishnaswamy, 1997;Blazer and Hybels, 2005;Onya and Stanley, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed in this study that, although they do not develop work activities, most the elderlies develop other types of activities in their daily life. On the other hand, evidence suggests significant associations between the Mental Health dimension of QOL and the employment status (P = 0.005) [27], becoming a matter of concern, since it reveals its influence in QOL, and may be related to the lower percentage of QOL attributed to the mental health dimension in this study.…”
Section: Discussionmentioning
confidence: 61%
“…This study, which included 349 elderly people in a self-training program in Masjed Sulaiman, aimed at generating behavioral changes related specially to balanced diet, physical activity and self-care through lectures and demonstrations, observed improvement in all dimensions of QOL with statistical significance after training (p <0.001) as measured by SF-36 [32].…”
Section: Discussionmentioning
confidence: 99%